Application of The Building Infill Concept in New Buildingswithin the Historic Semarang Old Town Area - PRAMESTI, CIPTETY TRISYA; SARDJONO, AGUNG BUDI (Jurnal Teknik Sipil dan Perencanaan, 2025)
The Old City of Semarang, as a national-level cultural heritage site, has inherited its function as a cultural center with unique architecture and urban layout that has remained. Over time, the development of the economy and high tourism demands exert significant pressure on the city's heritage. New functions with their commercialism often lead to inappropriate new buildings that potentially threaten the historic area's authenticity. Applying the infill building concept becomes a conservation solution that emphasizes optimizing vacant spaces in well-developed urban areas, including historic areas. Research has been conducted on several new buildings in the Semarang Old City that have changed in function and physical appearance. This research aims to analyze the existing conditions of new buildings and examine how infill development can be applied to structures in historical areas without damaging the architectural characteristics. The method employed includes descriptive analysis of observed objects by observing buildings, analyzed based on elements within the building infill approach. The results indicate that applying infill building in new constructions in the Old Town area requires a sensitive design approach, considering several elements, including mass, height, material color, ornamentation, and harmonious integration with the surrounding historical buildings. Additionally, it is suggested to the government that this research can initiate more detailed policies and active supervision regarding the construction of new buildings to maintain their authenticity. In conclusion, building infill can be an effective solution to support the economic development of historical areas without compromising cultural heritage, provided it is carried out with proper planning and regulations.